Humming - Kim, Suk-Jun (New York, NY : Bloomsbury Academic, 2019)
"From a gentle and soothing voice that is personal and intimate to hums that are mystical, impersonal and maddening, this book provides an anthropology of the concept of humming through the discipline of sound studies"--
'My hums? ... just about hums?' -- The secrecy of humming -- Hums of the other
Includes bibliographical references and index.
Keywords: Humming -- Philosophy; Humming -- Anthropological aspects